A preclinical study of Elettaria cardamomum for its antianxiety activity in Wistar albino rats - Prathima K Shetty,; Megha Rani N,; Rejeesh EP,; Rao SN, (Asian Journal of Medical Sciences, 2023)
Background: Elettaria cardamomum, commonly known as cardamom, is one of the most widely used spices worldwide and is conventionally well known for its effects on the central nervous system (CNS) as a food additive. Aims and Objectives: This study was carried out to assess the ethanolic extract of E. cardamomum (EEEC) for its CNS activity in rats. The purpose of this study was to validate the traditional use of E. cardamomum as an antianxiety agent. Materials and Methods: The elevated plus maze and light–dark arena models were used to evaluate its anxiolytic activity. The open field test and actophotometer were used for assessing its effect on locomotor activity. The experiments were performed in Wistar albino rats of either sex after grouping the animals into three different groups. Twelve animals per group were used. Distilled water (10 mL/kg) was used as Control and Diazepam (1 mg/kg) were used as standard drugs for the respective tests. Results: EEEC (at a dose of 100 mg/kg) has shown anxiolytic and reduced locomotor activity. Conclusion: The results of this study indicate that EEEC has anxiolytic and sedative effects, similar to benzodiazepine and possibly similar mechanisms.